(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Accurate accounting of natural gas consumption in residential sectors is essential for minimizing resource wastage, reducing financial losses, and ensuring fair billing practices. This article identifies the primary causes of volume discrepancies, including metering errors, gas leaks, unauthorized usage, and pressure variations. Proposed solutions, such as upgrading to smart meters, regular maintenance, pipeline modernization, improved monitoring systems, and stricter regulations, are discussed to mitigate these issues. The implementation of these measures not only enhances operational efficiency but also fosters transparency and trust between service providers and consumers. Furthermore, the article highlights the environmental and financial benefits of adopting advanced technologies and collaborative approaches. By addressing these challenges, stakeholders can contribute to a sustainable and efficient natural gas distribution system.